2017
DOI: 10.1109/tvcg.2016.2532329
|View full text |Cite
|
Sign up to set email alerts
|

PlenoPatch: Patch-Based Plenoptic Image Manipulation

Abstract: Patch-based image synthesis methods have been successfully applied for various editing tasks on still images, videos and stereo pairs. In this work we extend patch-based synthesis to plenoptic images captured by consumer-level lenselet-based devices for interactive, efficient light field editing. In our method the light field is represented as a set of images captured from different viewpoints. We decompose the central view into different depth layers, and present it to the user for specifying the editing goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…In Ref. [24], Zhang et al extended patch-based synthesis to plenoptic images captured by consumer-level lenslet-based devices for interactive light field editing. They represented the light field as a set of images captured from different viewpoints and performed patch-based image synthesis on all affected layers of the central view, and then propagated the edits to all other views.…”
Section: Patch-based Synthesismentioning
confidence: 99%
“…In Ref. [24], Zhang et al extended patch-based synthesis to plenoptic images captured by consumer-level lenslet-based devices for interactive light field editing. They represented the light field as a set of images captured from different viewpoints and performed patch-based image synthesis on all affected layers of the central view, and then propagated the edits to all other views.…”
Section: Patch-based Synthesismentioning
confidence: 99%
“…One way to look at light fields is as an image array with many different camera viewpoints. Zhang et al [53] demonstrated a layered patch-based synthesis system which is designed to manipulate light fields as an image array. This enables users to perform inpainting, and re-arrange and re-layer the content in the light field as shown in Fig.…”
Section: Image Collectionsmentioning
confidence: 99%
“…For large image datasets, Gould and Zhang [56] proposed a method to build a matching graph using PatchMatch, and optimize a conditional Markov random field to propagate pixel labels to all images from just a small subset of annotated Fig. 7 Results of reshuffling and re-layering the content in a light field using PlenoPatch [53]. Reproduced with permission from Ref.…”
Section: Image Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an estimated depth map they observe only a few differences on the capacity of the users to perform the editing. Assuming that light field data can be well approximated by a fixed number of scene layers at different depth, a depth-layer-aware image synthesis method is proposed in [14] for edit propagation.…”
Section: Introductionmentioning
confidence: 99%